2023
DOI: 10.1021/acs.joc.3c00708
|View full text |Cite
|
Sign up to set email alerts
|

BODIPYs with Chalcogenophenes at Boron: Synthesis and Properties

Abstract: Reported herein are the synthesis and characterization of BODIPYs bearing heterocycles at boron. To synthesize this series, various chalcogenophenes (furan, thiophene, selenophene, and tellurophene) were lithiated and then used as nucleophiles to attack the boron center of a parent F-BODIPY. Compounds in the series were compared with respect to their photophysical and structural properties, and trends were discussed. By virtue of the "heavy atom effect", as the mass of the heterocycle appended to the BODIPY co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…in THF at room temperature. 6 After five minutes, and in order to promote double-substitution of the fluoro substituents, the requisite F-BODIPYs (Scheme 1, 3 ) were added dropwise over five minutes to the pale-yellow stirring solution of 2-tellurophenyllithium. The resulting solution was stirred for one hour at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…in THF at room temperature. 6 After five minutes, and in order to promote double-substitution of the fluoro substituents, the requisite F-BODIPYs (Scheme 1, 3 ) were added dropwise over five minutes to the pale-yellow stirring solution of 2-tellurophenyllithium. The resulting solution was stirred for one hour at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Employing this synthetic method, a series of [Te]-BODIPYs that feature various substituents on the dipyrrinato backbone was synthesised (Table 1). The properties of the ethyl-substituted [Te]-BODIPY 2 have been established, 6 and it was found that replacing ethyl chains with octyl chains ( 4a ) had little effect on the system in terms of yields and ease of purification. Similarly, alkyl groups are well tolerated in the meso position of the dipyrrinato core, as demonstrated by the isolation of the methyl and isopropyl examples 4b and 4c , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations